Peran Komunikasi Interpersonal di Whatsapp ODOJ dalam Memotivasi Minat baca Al-Qur’an di kalangan Anggotanya - Nabila Maharani; Ahmad Mulyadi Kosim (Institut Agama Islam Nasional Laa Roiba Bogor, 2022)
Interpersonal communication is the process of transmission and acceptance of a message done by the messenger with the recipient both directly and indirectly. Motivation has a role in the process of reading the Al-quran for members of organizations such as odoj (one day one juz) that could be compared to fuel to the fuel that runs within each individual in reading the Al-quran. The needed role of motivation was needed in the Al-quran reading activity in the odoj community (one day one juz). A member's difficulty in dividing his time in reading the Al-quran until it is late and does not report to read the Al-quran in a single day. This is due to lack of motivation and the difficulty with managing time. Therefore, the odoj community (one day one juz) community leaders apply interpersonal communication to motivate members to read the Al-quran one juz in one day. Researchers are therefore interested in research on the role of interpersonal communication in the whatsapp odoj (one day one juz) in moving interest in reading the Al-quran among its members.The type of research in this thesis writing is field research a descriptive qualitative study. The population in this study is 30 people and the sample in this study is 15 members, and 3 stewards of the odoj community (one day one juz). This data-collection technique uses interviews and documenting methods, using a descriptive analysis or written words, Oral, and observational behaviors. And the data analysis used based on descriptive analysis, it is divided into three of reduction, data presentation and data conclusions. The result of this research is that the role of interpersonal communication is taking place online using whatsapp media, giving motivation in the whatsapp group, offering advice and enthusiasm so that its members can complete their activities in reading the quran juz in one day. As for the factor that influences the role of interpersonal communication in motivating its members is the difficulty of managing time in the reading of the Al-quran, the laziness that always comes. Keywords : Interpersonal communication, motivation, reading the qur 'an, odoj (one day one juz)